Creating the asset base – a review of literature and policy on housing with care. Issue 1 (12th March 2014) - June Atkinson, Teresa; Evans, Simon; Darton, Robin; Cameron, Ailsa; Porteus, Jeremy; Smith, Randall
Abstract : Purpose: – Appropriate housing for the growing population of older adults is becoming an international concern. The purpose of this paper is to report on a review of UK and international literature carried out as part of a project exploring the commissioning and delivery of social care in housing with care settings. The paper also considers housing with care in the context of UK policy and practice. Design/methodology/approach: – The peer literature review process used a range of academic databases as well as government and third sector web sites, drawing on relevant material in English published from 1990 to 2012. Findings: – Findings are presented within three main themes: how care and support is provided; the role of the built environment; and the benefits for resident well-being. The review found a paucity of literature focusing specifically on care and support in housing with care settings, particularly in terms of how social care is delivered, but the evidence base suggests that housing with care is in a strong position to deliver on most if not all UK government aspirations. Practical implications: – Despite a growing literature both in the UK and internationally exploring the characteristics and benefits of housing with care for older people, substantial gaps remain in the research evidence. Originality/value: – This paper presents an up to date review of the housing with care literature in the context of current UK policy.